Association Between Paternal Age and Birth Weight in Preterm and Full-Term Birth: A Retrospective Study - Mao, Yiting; Zhang, Chen; Wang, Yinyu; Meng, Yicong; Chen, Lei; Dennis, Cindy-Lee; Sheng, Jianzhong; Wu, Yanting; Huang, Hefeng (Frontiers in Endocrinology, 2021)
Purpose: While it is well documented that maternal adverse exposures contribute to a series defects on offspring health according to the Developmental Origins of Health and Disease (DOHaD) theory, paternal evidence is still insufficient. Advanced paternal age is associated with multiple metabolism and psychiatric disorders. Birth weight is the most direct marker to evaluate fetal growth. Therefore, we designed this study to explore the association between paternal age and birth weight among infants born at term and preterm (<37 weeks gestation). Methods: A large retrospective study was conducted using population-based hospital data from January 2015 to December 2019 that included 69964 cases of singleton infant births with complete paternal age data. The primary outcome was infant birth weight stratified by sex and gestational age including small for gestational age (SGA, 10th percentile) and large for gestational age (LGA, 90th percentile). Birth weight percentiles by gestational age was based on those published in INTERGROWTH-21st neonatal weight-for gestational-age standard. Logistic regression analysis and linear regression model was used to estimate the association between paternal age and infant birth weight. Results: Advanced paternal age was associated with a higher risk for a preterm birth (35-44years: adjusted odds ratio (OR)=1.13, 95%CI (1.03 to 1.24); >44 years: OR=1.36, 95%CI (1.09 to 1.70)). Paternal age exerted an opposite effect on birth weight with an increased risk of SGA among preterm infants (35-44years: OR=1.85, 95%CI (1.18 to 2.89) and a decreased risk among term infant (35-44years: OR=0.81, 95%CI (0.68 to 0.98); >44 years: OR=0.50, 95%CI (0.26 to 0.94). U-shaped associations were found in that LGA risk among term infants was higher in both younger (<25 years) (OR=1.32; 95%CI, 1.07 to 1.62) and older (35-44 years) (OR=1.07; 95% CI, 1.01 to 1.14) fathers in comparison to those who were 25 to 34 years old at the time of delivery. Conclusions: Our study found advanced paternal age increased the risk of SGA among preterm infants and for LGA among term infants. These findings likely reflect a pathophysiology etiology and have important preconception care implications and suggest the need for antenatal monitoring.